2020
DOI: 10.3389/feduc.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Argue From Others’ Erroneous Arguments – Fostering Argumentation Competence Through Learning From Advocatory Errors

Abstract: Argumentation competence is an essential skill to be acquired in university education. However, there is a lack of advanced argumentation competence even for graduate students. To foster argumentation competence, typical interventions focus on examplebased learning. Another approach is learning from advocatory errors. The combination of both approaches is presenting examples of erroneous arguments. Drawing on the concept of case-based learning, we developed a learning intervention that presents examples of arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Especially, domain-specific epistemological beliefs seem to be important for the application of advanced argumentation strategies (Iordanou et al, 2016). A recent study by Klopp and Stark (2020) revealed that undergraduate psychology students have rather low scientific argumentation skills (cf., Astleitner et al, 2003). As summarized by Klopp and Stark (2020), students make typical argumentation errors, some of which also relate to epistemological issues, e.g., not giving any justification or evidence for a claim or deficits in the acknowledgment of different perspectives on a certain topic (cf., Fischer et al, 2014).…”
Section: Epistemological Beliefs In Psychologymentioning
confidence: 99%
“…Especially, domain-specific epistemological beliefs seem to be important for the application of advanced argumentation strategies (Iordanou et al, 2016). A recent study by Klopp and Stark (2020) revealed that undergraduate psychology students have rather low scientific argumentation skills (cf., Astleitner et al, 2003). As summarized by Klopp and Stark (2020), students make typical argumentation errors, some of which also relate to epistemological issues, e.g., not giving any justification or evidence for a claim or deficits in the acknowledgment of different perspectives on a certain topic (cf., Fischer et al, 2014).…”
Section: Epistemological Beliefs In Psychologymentioning
confidence: 99%
“…This statement is in line with Sitzman et al (2015), who stated that prior knowledge has a very important role in the correction of errors. It also affects argumentation skills (Klopp & Stark, 2020). Accordingly, students will likely be unable to analyze errors if they lack the appropriate prior knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…(Oser, 2007). Wagner et al (2014cf., Klein, Wagner, Klopp, & Stark, 2017;Klopp & Stark, 2020) showed that learning from advocatory errors effectively fostered student teachers' skills to explain authentic school situations using scientific theories.…”
Section: The Concept Of Scientific Explanations and Methods To Foster...mentioning
confidence: 99%